2020
DOI: 10.1111/ijlh.13164
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobins F, A2, and E levels in Laotian children aged 6‐23 months with Hb E disorders: Effect of age, sex, and thalassemia types

Abstract: Introduction: Determination of hemoglobins (Hbs) F, A 2, and E is crucial for diagnosis of thalassemia. This study determined the levels of Hbs F, A 2, and E in children aged 6-23 months and investigated the effect of age, sex, and types of thalassemia on the expression of these Hbs.Methods: A total of 698 blood samples of Laotian children including 272 non-Hb E, 271 Hb E heterozygotes, and 155 Hb E homozygotes were collected. Hb profiles were determined using the capillary zone electrophoresis. Coinheritance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Despite insignificance, infants with two α-globin gene defects displayed reduced HbA 2 and modestly increased HbF levels in the previous study. 9 The decrease in HbA 2 levels was clearly noticed in infants with three α-globin gene defects or deletional HbH disease in our study. Together, the results suggested that HbA 2 levels may be considered as valuable markers for the inheritance of globin gene defects in infants.…”
Section: To the Editorsupporting
confidence: 62%
“…Despite insignificance, infants with two α-globin gene defects displayed reduced HbA 2 and modestly increased HbF levels in the previous study. 9 The decrease in HbA 2 levels was clearly noticed in infants with three α-globin gene defects or deletional HbH disease in our study. Together, the results suggested that HbA 2 levels may be considered as valuable markers for the inheritance of globin gene defects in infants.…”
Section: To the Editorsupporting
confidence: 62%
“…Haemoglobin (Hb) A 2 (α2δ2) is a minor haemoglobin with levels between 2.5% and 3.5% of total circulating haemoglobin in healthy adults 25. In this study, all family members except the proband had a detectable HbA 2 (αδ) peak on the CE plots (figure 3).…”
Section: Discussionmentioning
confidence: 57%
“…[14] Childhood HB has a dual blood supply of hepatic artery and portal vein, and HB tissues are predominantly supplied by the hepatic artery, but both have portal vein involved in blood supply. [15] If pediatric HB patients are treated with hepatic artery embolization alone, tumor portal vein blood supply may still lead to tumor residual and recurrence. [16] The iodine oil deposited in the tumor may dissociate with the blood flow of the dual blood supply to the liver and affect the efficacy.…”
Section: Discussionmentioning
confidence: 99%